1998
DOI: 10.1128/jcm.36.10.2869-2873.1998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida dubliniensis Isolates in a Yeast Stock Collection

Abstract: To establish the historical prevalence of the novel yeast species Candida dubliniensis, a survey of 2,589 yeasts originally identified as Candida albicans and maintained in a stock collection dating back to the early 1970s was undertaken. A total of 590 yeasts, including 93 (18.5%) β-glucosidase-negative isolates among 502 isolates that showed abnormal colony colors on a differential chromogenic agar and 497 other isolates, were subjected to DNA fingerprinting with the moderately repetitive sequence Ca3. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 23 publications
9
90
2
1
Order By: Relevance
“…A delayed appearance of blue green halo surrounding the colonies observed after the fourth day onwards unlike C. albicans 5 suggests the atypical nature of these isolates. The formation of purplish tinge observed on the ninth day of incubation of group I isolates is in agreement with Odds et al 19 who also reported similar change in color of typical chlamydospore-positive C. albicans after prolonged incubation.…”
Section: Discussionsupporting
confidence: 91%
“…A delayed appearance of blue green halo surrounding the colonies observed after the fourth day onwards unlike C. albicans 5 suggests the atypical nature of these isolates. The formation of purplish tinge observed on the ninth day of incubation of group I isolates is in agreement with Odds et al 19 who also reported similar change in color of typical chlamydospore-positive C. albicans after prolonged incubation.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that this novel species is widespread, most probably extending across the globe [7]. One recent study investigating the prevalence of C. dubliniensis in a yeast stock culture collection (overall prevalence of 2.1%) suggested that it is also present in healthy individuals and not restricted to gastrointestinal sites [8]. Furthermore, C. dubliniensis was assessed as the second most abundant species after C. albicans isolated from the oral cavity of insulin-using diabetes mellitus patients for both carriers of and those a¡ected by the fungus [9].…”
Section: Introductionmentioning
confidence: 99%
“…incorrectly identified as C. albicans 10,11 and in another study of oral yeasts isolated from HIV infected individuals, 16.5% of C. dubliniensis isolates was incorrectly identified as C. albicans. 12 Due to the demand of clinical diagnostic laboratories for accurate, reliable, inexpensive and rapid identification techniques which can be applied to large numbers of samples, several phenotype-based tests are available to differentiate between these species.…”
Section: Introductionmentioning
confidence: 99%